Mitochondrial-targeted DNA repair enzyme 8-oxoguanine DNA glycosylase 1 protects against ventilator-induced lung injury in intact mice - Hashizume, Masahiro (American Physiological Society, 2013)
This study tested the hypothesis that oxidative mitochondrial-targeted DNA (mtDNA) damage triggered ventilator-induced lung injury (VILI). Control mice and mice infused with a fusion protein targeting the DNA repair enzyme, 8-oxoguanine-DNA glycosylase 1 (OGG1) to mitochondria were mechanically ventilated with a range of peak inflation pressures (PIP) for specified durations. In minimal VILI (1 h at 40 cmH(2)O PIP), lung total extravascular albumin space increased 2.8-fold even though neither lung wet/dry (W/D) weight ratios nor bronchoalveolar lavage (BAL) macrophage inflammatory protein (MIP)-2 or IL-6 failed to differ from nonventilated or low PIP controls. This increase in albumin space was attenuated by OGG1. Moderately severe VILI (2 h at 40 cmH(2)O PIP) produced a 25-fold increase in total extravascular albumin space, a 60% increase in W/D weight ratio and marked increases in BAL MIP-2 and IL-6, accompanied by oxidative mitochondrial DNA damage, as well as decreases in the total tissue glutathione (GSH) and GSH/GSSH ratio compared with nonventilated lungs. All of these injury indices were attenuated in OGG1-treated mice. At the highest level of VILI (2 h at 50 cmH(2)O PIP), OGG1 failed to protect against massive lung edema and BAL cytokines or against depletion of the tissue GSH pool. Interestingly, whereas untreated mice died before completing the 2-h protocol, OGG1-treated mice lived for the duration of observation. Thus mitochondrially targeted OGG1 prevented VILI over a range of ventilation times and pressures and enhanced survival in the most severely injured group. These findings support the concept that oxidative mtDNA damage caused by high PIP triggers induction of acute lung inflammation and injury.